PRACTICE OF CHESS FOR STUDENTS OF SECOND YEAR OF EDUCATION OF A PUBLIC SCHOOL: A POSITIVE EXPERIENCE (Fiep Bulletin - online, 2011)
This study sought to determine how the practice of chess can be used as a pedagogical tool in a second year of elementary school, a state school education in Caxias do Sul, and their contribution in developing the moral aspects the students. It is known that the games are very important in learning and development of students, and practice of chess provides among other abilities, reflection, concentration, strategy, respecting the rules, and can be practiced regardless of age and sex, and have not contraindications. The lessons of chess to 28 students began in May 2010 and conducted in a specific room, on Tuesdays and lasted approximately 45 minutes. As a methodology, classes were taught by means of intervention activities, lifting of problem situations, explanations about the rules of the game, the moves and catches parts, activities, memorization of movements, and pre-game introductory sports and the game of chess itself. Also in all classes was emphasized respect for rules, the importance of respect for others and other aspects related to attitudes and values essential to the practice of games and sports. We believe that the practice of chess school has assisted in student learning, whether in the moral aspects and relationships, as well as subsidies for the other disciplines, and prove effective at creating links between knowledge experienced in teaching and coexistence learners, thereby strengthening the relevant pedagogical importance of a chess game.
Keywords: chess school; teaching tool; development of values